Bis{(E)-N′-[2,4-bis(trifluoromethyl)benzylidene]isonicotinohydrazide} monohydrate - H. S. Naveenkumar; Amirin Sadikun; Pazilah Ibrahim; Chin Sing Yeap; Hoong-Kun Fun (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, 2C15H9F6N3O·H2O, contains two independent Schiff base molecules and one water molecule. Both Schiff base molecules exist in an E configuration with respect to the C=N double bonds and the dihedral angles between the benzene and the pyridine rings in the two molecules are 17.53 (12) and 20.62 (12)°. In the crystal structure, molecules are linked by intermolecular N—H...O and C—H...O hydrogen bonds into infinite one-dimensional chains along the a axis. In addition, intermolecular O—H...N, O—H...F, C—H...F and C—H...O hydrogen bonds further link these chains into a three-dimensional network. Weak π–π interactions with centroid–centroid distances in the range 3.6495 (17)–3.7092 (16) Å are also observed.